WEB BASED LIBRARY PROGRAM AT SMKN 8 BANDUNG - Muhammad Zacky Sudardjat; Ari Purno Wahyu Wibowo (Jurnal Darma Agung, 2022)
Library is part from source learn what to do owned by every school or college high. Because participants educate with easy find information or knowledge through library. With development technology make people think for could work more effective and efficient. One of them is with make system conventional becomes system computerization. Websites with utilise connected facilities with the internet. library can more effective and efficient in search and order book. In study this, I has designing web based system information use language PHP MySQL programming. With existence system this, hope could resolve various needs user for look for books and books as well as make it easy administration school in circulation loan book and creation report. From research that has conducted to thing the the author's results implement in design system information library web based at SMKN 8 BANDUNG.